Nekateri sociološki vidiki razširjenosti mobinga med učitelji v osnovni šoli - Bezenšek, Jana; Purgaj, Tjaša (Revija za elementarno izobraževanje, 2009)
Some sociological aspects of the spread of mobbing among teachers in elementary schools. The paper presents a discussion on the appearance of mobbing in different working environments in Slovene elementary schools. The research is based on empirical facts collected in three different schools as a type work organization. There are some differences between organizations in the frequencies that mobbing appears, victims’ characteristics, and the reasons and consequences that appear after the mobbing .The results of the empirical research on the psychosocial conditions in the work place show that more and more teachers as employees are mobbing victims. Mobbing is defined as a very strong social stress factor. Each individual or a social group experiences mobbing as a conflict situation that can involve communication at work. Attacked individuals, the victims of the conflict, are exposed to the permanent and long-term attacks of one or more people at work. The intention of these attacks is to oust the individual from the organization or to harm them in any other way. A lot of pressure is being put on these people and also intimidation, humiliation, molestation or some other negative influences appear. Because of the psychological burden caused by this, the victim usually becomes ill and often leaves the work position. Mobbing can affect the individual in a way that they are no longer capable for fitting in to any new work environment. The most frequent consequences that the victims suffered were: the feeling of being stressed, insomnia, concentration problems and family problems.